Variables impacting sanitation efficacy in university swine barns - Staggs, Alexander J.; Muckey, M.E.; Jones, Cassandra K. (My University, 2017)
Health is a primary concern for pork producers. It is essential to make sure barns are cleaned between groups of pigs to prevent horizontal disease transmission by using standard cleaning procedures. However, there is limited information if different surfaces are more or less challenging to clean and sanitize using industry-accepted methods. The goal of this experiment was to determine the efficacy of industry-accepted sanitation of finishing barns by measuring the bacterial load found on different surface types before and after cleaning. After removal of pigs, 53 locations (10 × 10cm2) were swabbed from two different finishing swine barns at the Kansas State University Swine Teaching and Research Unit. Barns were then powerwashed per industry-accepted procedures, including the use of an alkyl dimethyl benzyl ammonium chloride (26%) and glytaraldehyde (7%) cleaner-disinfectant (Synergize, Preserve International, Reno, NV). After sanitation and drying, swabs from paired locations were collected. The locations were classified by location, surface type, contact with feed, and contact with pigs. Swabs were blinded and analyzed for quantitative bacterial analysis by the Iowa State University Diagnostic Laboratory in Ames. Results were reported as 0: no presence of bacteria, 1: low bacterial contamination, 2: moderate bacterial contamination, or 3: heavy bacterial contamination. Samples containing bacteria were then characterized to the level of the genus. Data were analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC). Sanitation played a significant role in reducing (P < 0.05) the bacterial load of all the surface types except for concrete, where there was not a significant reduction in bacterial load (P > 0.05). The results also showed that sanitation reduced the bacterial load of animal contact locations and feed contact locations (P < 0.05). However, the bacterial load on feeder drops, feeders, and waterers were not significantly reduced by cleaning (P > 0.05). While sanitation reduced most bacterial species, it actually increased others, specifically Bacillus spp., Enterococcus spp., and Staphylococcus spp. This research reveals that while industry-accepted sanitation methods reduce overall bacterial loads in finishing barns, there are variations in its efficacy based on surface type and location. Further research is warranted to design and evaluate more effective sanitation methods to maximize swine health.
Keywords: Spring 2017